Domestic Violence Against Pregnant Women: Prevalence and Related Factors - Metin Pıçakçıefe; Şeyma Ata; Raziye Ülkü Kıcalı; M. Onur Vatandaş (Gazi Medical Journal)
Objective: Violence against women, especially during pregnancy, is a problem affecting the health of both the mother and fetus. The study evaluated the prevalence and associated factors of domestic violence in pregnant women who apply to a healthy life center (HLC). Methods: The population of the cross-sectional and analytical study, in which the surveillance data were analyzed, consisted of 202 pregnant women who applied to the HLC of the district health directorate. The SPSS 22.0 package program was used to analyze the data. The data was examined using Fisher’s exact test, Pearson’s chi-square and p<0.05 was considered statistically significant. Results: 2% of pregnant women were exposed to domestic violence before pregnancy and 5.4% of them were exposed to domestic violence during pregnancy. Of the participants, 0.5% were exposed to physical, 2.5% to verbal, 5% to psychological, 1.5% to economic, and 2.5% to social violence. Pregnant women living in rural areas (p=0.035), middle income (p=0.047), having a nuclear family structure (p=0.004), dissatisfaction with marriage life (p=0.001) and planned pregnancy (p=0.025) significantly increases the frequency of exposed to domestic violence. Conclusion: The most important result of our study is the low frequency of exposure of pregnant women to domestic violence during pregnancy. The most common type of violence is psychological violence. Healthcare professionals should question domestic violence during pregnancy while conducting anamnesis and conduct a detailed examination about violence.